Genotoxic factors associated with the development of receptor-negative breast cancer: potential role of the phenomenon of switching of estrogen effects - Berstein, L.M.; Tsyrlina, E.V.; Poroshina, T.E.; Levina, V.V.; Vasilyev, D.A.; Kovalenko, I.G.; Semiglazov, V.F. (Experimental Oncology, 2006)
Aim: About 30–40% of breast cancers lack steroid receptors (ER and/or PR) at diagnosis that worsen prognosis and limit the usage of hormone therapy. The aim of this paper has been to study the role of DNA-damaging factors as the potential modifiers of the receptor-negative tumors incidence. Materials and Methods: The investigation consisted of two principal parts. In one of them ER and PR content was measured in breast cancer samples from 2284 primary patients (350 of them — current or previous smokers). In separately studied subgroup of 1010 patients 95 suffered with diabetes mellitus type II. Results: As it was shown, smokers and diabetics carry more frequently (p < 0.05) tumors with phenotypes ER+PR- and PR- only in the group of women with conserved menstrual cycle that is in case of relatively higher estrogenic stimulation. In another part of the investigation immunohistochemical study of DNA damage marker — 8-hydroxy-2-deoxyguanosine (8-OH-dG) in 16 R(-) and 18 R(+) breast cancer specimens demonstrated more frequent positive staining in the former group of samples (p = 0.05). Besides, as it was revealed in breast cancer cell line MCF-7 the combination of estradiol with aryl hydrocarbonic receptors agonist beta-naphtoflavone induced pronounced genotoxic damage (by 8-OH-dG content) in association with the loss of ER. Conclusion: Thus, pro-genotoxic status (smoking, diabetes) and direct signs of genotoxic injury, in accordance with regularities of the phenomenon of switching of estrogen effects. can be reckoned among the factors promoting the development of receptor-negative breast cancer.